Immunity Rights of Experts Who Provide Statements in Trials (Study Decision No: 47/Pdt.G/LH/2018/PN Cbi) - Mansyah, Muh Sutri; Suhartono, Rizki Mustika; Salad, Hariasi; Dewi, Rasmala; Bimasakti, David Haryo (The Digest: Journal of Jurisprudence and Legisprudence, 2023)
This paper investigates the critical issue of immunity rights for experts who provide statements in trials, with a specific focus on the analysis of Decision No: 47/Pdt.G/LH/2018/PN Cbi. Employing a normative research approach, the study adopts a comprehensive methodology, encompassing a case and statutory perspective alongside grammatical and systematic interpretation. The pivotal finding of the research centers on the rejection of a lawsuit by the Panel of Judges, attributing it to the absence of relative competence in the presented case. Notably, the decision contains a notable directive, proposing that "experts in the future should have the right not to be prosecuted criminally." This forward-looking perspective accentuates the significance of extending immunity rights to experts. The paper underscores the urgent need for recognizing and formalizing these rights within the legal framework, advocating for the incorporation of immunity provisions for experts in the Witness and Victim Protection Law. The research contributes to the broader discourse on legal reforms, highlighting the evolving landscape concerning the legal status and protection of experts involved in legal proceedings. In navigating these complex legal dynamics, this paper calls for a proactive approach from policymakers and legislators to address and safeguard the immunity rights of experts, ensuring a fair and conducive environment for their participation in legal processes.